2014
DOI: 10.1007/s10802-014-9947-9
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Links Between Perfectionism and Depression in Children

Abstract: Alliance; www.mac-cura.ca), and Fonds québécois de la recherche sur la société et la culture (FQRSC).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
39
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 84 publications
(144 reference statements)
6
39
0
2
Order By: Relevance
“…This is because the only statistically significant cross-lagged effect was depressive symptoms to SPP. This is a finding that directly replicates another study testing a reciprocal relations model between SPP and depression (Asseraf & Vaillancourt, 2015). On the basis of our findings, we tentatively suggest that the current study provides the first evidence of a complication/scar model to explain the relationship between perfectionism and depression in youth soccer players.…”
Section: The Relationship Between Perfectionism and Depressionsupporting
confidence: 89%
See 3 more Smart Citations
“…This is because the only statistically significant cross-lagged effect was depressive symptoms to SPP. This is a finding that directly replicates another study testing a reciprocal relations model between SPP and depression (Asseraf & Vaillancourt, 2015). On the basis of our findings, we tentatively suggest that the current study provides the first evidence of a complication/scar model to explain the relationship between perfectionism and depression in youth soccer players.…”
Section: The Relationship Between Perfectionism and Depressionsupporting
confidence: 89%
“…In another study, Asseraf and Vaillancourt (2015) also found support for a complication/scar model in that depression positively predicted SPP in adolescents over a two year period. We are not aware of any evidence from longitudinal studies in sport that support a complication/scar model.…”
Section: Models Of Relationships: Perfectionism Burnout and Depressionmentioning
confidence: 82%
See 2 more Smart Citations
“…Se ha demostrado que cuando las madres tienen altas frecuencias de control, directividad, crítica y conductas perfeccionistas, ponen injustificada presión a sus hijos (Hyson, Hirsh-Pasek, Rescorla, Cone, & Martell-Boinske, 1991). Asimismo, se muestra evidencia de su relación con otras variables como la depresión (Asseraf & Vaillancourt, 2015;Huggins, Davis, Rooney, & Robert, 2008;Hewitt et al, 1996), la formación del autoconcepto (Rice, Kubal, & Preusser, 2004;Shafran et al, 2002), la baja autoestima (Rutsztein, Scappatura, & Murawski, 2007), los altos niveles ansiedad (Essau, Leung, Conradt, Cheng, & Wong, 2008;Affrunti & Woodruff-Borden, 2015), la agresividad (García-Fernández, Vicent, Cándido, Gonzálvez, & Sanmartín, 2016), los afectos negativos (Vicent, Inglés, Gonzálvez, Sanmartín, & García-Fernández, 2016) y se muestra como un factor de riesgo para adquisición de trastornos alimenticios en la adolescencia (Pamies & Quiles, 2014).…”
Section: Introductionunclassified